Bacteraemia in Maiduguri Metropolis, Nigeria: A 2005 to 2009 study of some causative pathogens and fluoroquinolones activities against them - Ohieku John David, Rilwanu Aminu Magaji, Duru Christian (Journal of Applied Pharmaceutical Science)
Blood-stream pathogens were investigated between 2005 and 2009 in 262 patients with septicaemia in Maiduguri Metropolis, Nigeria to evaluate trends in fluoroquinolones activities against them. Blood samples were cultured in an enriched nutrient agar while susceptibilities tests were performed using the disc diffusion techniques.Staphylococcus aureus, the predominant pathogen accounted for 57.6% and peaking in 2007 with 26.5%. Salmonella spp (overall: 20.2%) infectivity increased from 2006-2008 by 15% but Klebsiella bacteraemia (14.9%) decreased by 20.7% from 2006-2008. Bacteraemia caused by Escherichia coli (7.3%) was the least. The S. aureus sensitivity to ciprofloxacin decreased by 25% between 2005 and 2007 while ofloxacin steady decrease from 2005 to 2008 by 33% showed significant correlation (P
Keywords: Bacteraemia, ciprofloxacin, fluoroquinolones, Staphylococcus aureus, Pathogens, nalidixic-acid resistant.